Violation of Advertising Ethics in Emeron Lovely Uv White Compact & Loose Powder Ads - Shidqi Pratama Buana Firdaus, Achmad; Az-Zahra Rahmawati, Annisa (Educationist: Journal of Educational and Cultural Studies, 2023)
In this modern era, there are various types of advertising in the media, each brand has its own uniqueness to increase brand awareness and build a brand image that is increasingly attractive to consumers. The importance of building a brand image in order to increase customer loyalty, one of which is Emeron's ad, where the 31-second ad displays an SPF value in the ad which has violated the code of ethics in the Indonesian Pariwara Ethics. So, in this study, researchers discussed "Emeron Lovely UV White Compact & Loose Powder". The method used in this research is observation and documentation, it is said that there is a code of ethics against Indonesian Advertising Ethics. Making advertisements is of course very procedure to the Indonesian Advertising Ethics, so that the advertisements produced have good ethics in them.